2005
DOI: 10.1038/sj.bjc.6602733
|View full text |Cite
|
Sign up to set email alerts
|

Capecitabine and mitomycin C as third-line therapy for patients with metastatic colorectal cancer resistant to fluorouracil and irinotecan

Abstract: Protracted venous infusion 5-fluorouracil (5FU) combined with mitomycin C (MMC) has demonstrated significant activity against metastatic colorectal cancer. Owing to potential synergy based upon upregulation of thymidine phosphorylase by MMC, the combination of capecitabine and MMC may improve outcomes in irinotecan-refractory disease. Eligible patients with progressive disease during or within 6 months of second-line chemotherapy were treated with capecitabine (1250 mg m À2 twice daily) days 1-14 every 3 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 16 publications
0
40
0
Order By: Relevance
“…The 'ethical condition' to evaluate the clinical effect of an irinotecan metronomic treatment in this patient population depended on the fact that there was no evidence that a third/fourth line of chemotherapy could produce an improvement in terms of clinical benefit or efficacy in patients with mCRC already treated with both oxaliplatin-and irinotecan-based chemotherapy. The results of several phase II clinical studies showed that a third/fourth line of fluoropyrimidine-based chemotherapy in this setting of patients generally produces a poor response rate (around or less than 10%), with a median PFS between 2 and 3 months and with a median OS of approximately 6 -9 months (Chong et al, 2005;McCollum et al, 2006;Scartozzi et al, 2006). Besides the weak antitumour activity, these treatments are limited by a substantial toxicity Xgrade 3 (NCI scale) reported in about 10 -15% of all patients.…”
Section: Discussionmentioning
confidence: 99%
“…The 'ethical condition' to evaluate the clinical effect of an irinotecan metronomic treatment in this patient population depended on the fact that there was no evidence that a third/fourth line of chemotherapy could produce an improvement in terms of clinical benefit or efficacy in patients with mCRC already treated with both oxaliplatin-and irinotecan-based chemotherapy. The results of several phase II clinical studies showed that a third/fourth line of fluoropyrimidine-based chemotherapy in this setting of patients generally produces a poor response rate (around or less than 10%), with a median PFS between 2 and 3 months and with a median OS of approximately 6 -9 months (Chong et al, 2005;McCollum et al, 2006;Scartozzi et al, 2006). Besides the weak antitumour activity, these treatments are limited by a substantial toxicity Xgrade 3 (NCI scale) reported in about 10 -15% of all patients.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, we would like to reiterate our comments in the discussion that this regimen represents a viable option for patients with metastatic colorectal cancer who have previously received fluorouracil and irinotecan (Chong et al, 2005). The results of our study should not necessarily be extrapolated to patients who have previously received oxaliplatin or targeted agents.…”
Section: Sirmentioning
confidence: 88%
“…Combination with MMC resulted in a response rate of 15% in irinotecan-resistant cancer, but its efficacy fell to 5% when the cancer was resistant to both irinotecan and oxaliplatin. Other combinations with trimetrexate or irinotecan did not show any additional benefit either (Chong et al, 2005;Gubanski et al, 2005;Matin et al, 2005).…”
Section: Discussionmentioning
confidence: 98%